Reconciliation Once and For All: Economic Impact Evaluation and Social Cost Benefit Analysis - Banerjee, Onil (2017)
This paper makes two contributions to the debate on the compatibility of social cost benefit analysis and economic impact analysis. First we argue that benefits estimated through economic impact analysis are amenable to subsequent analysis in a social cost benefit framework when household utility is used as the measure of welfare. Second, economic impact analysis and social cost benefit analysis of investment loans may be evaluated from the perspective of the multilateral lender and from that of the beneficiary government. While the first is straightforward to implement, this paper develops an approach to evaluating the investment from the perspective of the beneficiary government which internalizes the repayment of the loan within the economic impact model itself. We compare these two perspectives by undertaking an economic impact and social cost benefit analysis of a US$6.25 million tourism investment in Uruguay.